Comparison of Liquid Product Characteristics of PFAD Metal Soap Decarboxylation by Batch and Continuous Process - Godlief F. Neonufa; Lidya Elizabeth; Endar Puspawiningtiyas; Astri Nur Istyami; Ronny Purwadi; Tatang H. Soerawidjaja; Meiti Pratiwi (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Well-run continuous processes will benefit the industrial world in the future. This paper investigated the effect of batch and continuous processes on metal basic soap decarboxylation in terms of the liquid product characteristics. The metal soap used in the process was made from palm fatty acid distillate (PFAD) reacted with mixed metal oxides of Zn, Mg, and Ca. While the batch decarboxylation was carried out in a batch reactor at 400 °C for 5 hours, the continuous decarboxylation was conducted at 400 °C with a feed flow rate of 3.75 gr/minutes. Theoretically, the yield of batch decarboxylation is 76.6 wt% while the yield of continuous decarboxylation is 73.37 wt%. The liquid product was fractionated to separate short-chain hydrocarbon of C7-C10 (gasoline fractions) from medium- to long-chain hydrocarbons, or greater than C11 (green diesel fraction). The result showed that the alkane content from the batch process was higher than from the continuous process, whereas the continuous process produced more ketone products compared to the batch process. Furthermore, the GC-FID analysis showed a similar amount of total hydrocarbon (alkane, iso-alkane, and alkene) in both the batch and the continuous process.